The Pornography of Violence on Social Media: A Reception Analysis on User Experiences in the case of the Ukraine-Russia War - Selman Selim Akyüz; Fatma Öztat (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The relationship between the transmission of social reality in the media and the application of ethical rules is one of the important topics of discussion in the production and distribution processes of messages in mass media. With the emergence of social media, the effects of uncontrolled violent images on users are the subject of research. An important question is whether the publication of violent images leads to awareness or to the normalization or encouragement of violence. In this study, reception analysis was made in the context of the images of violence that spread uncontrollably on social media platforms in Turkey during the Ukraine-Russia War. Two violent images were shown to 13 participants with different demographic characteristics. The reactions and thoughts of the participants towards the images were revealed by semi-structured interview method. Most of the participants stated that the images were disturbing and that violence was not acceptable in any way. Most of the participants stated that watching the images of violence caused them to develop feelings such as sadness, fear, anxiety and pity as a result of empathy, that the publication of these images would not provide any benefit. A small number of respondents stated that they did not see a problem with resorting to violence in certain situations.